PAKOM PENGEMBANGAN RENCANA PELAKSANAAN PEMBELAJARAN (RPP) BERDASARKAN KURIKULUM 2013 DI PCM KECAMATAN MATESIH KARANGANYAR - Santoso, Joko; Rahmawati, Laili Etika; Muhroji, Muhroji; Pradana, Rizka Rahma; Untari, Rina (Universitas Muhammadiyah Surakarta, 2015)
This public service has aim to give knowledge for the MIMâs teachers in Matesih subregency about the curriculum of 2013 paradigm, continued profession development, and the lesson plan development based on the curriculum of 2013. The strategies used to pursue the goals were: (1) discussion: in the beginning of the activities, all oftheÂ participants wereÂ seated inÂ a roomÂ to getÂ the knowledgeÂ of curriculumÂ 2013 paradigm and the continued profession development. After the presentation delivered by the speaker has finished, the participants conducted the discussion with the speaker related to the knowledge which had not been understood yet; (2) the lesson planworkshop: after the discussion finished, the participants were divided into two groups. The division of the groupsÂ based on the class grade, they were classÂ 1, 2, and 3 belonging to the first group while the class 4, 5, and 6 were belonging to the second group. Every group was guided by an instructure to give gudance for the participantsto understand the lesson plan format based on the curriculum of 2013 and asked to practiceÂ theÂ lessonÂ plaan arranging.Â The resultÂ ofÂ theÂ competitive socialÂ service program (PAKOM) for the MIMâs teachers in Matesih subregency can be stated as successful. The indication was the target reached e.i. 100% of the teachers couldconstruct the lesson plan based on the curriculum of 2013.